Patient Satisfaction with Health Services (in the Building) at Jajaway Health Center Bandung City - Fauziyah, Rahmah; Rejeki, Yunita Fitri; Herdian, Fitra (LPPM STIKes Muhammadiyah Ciamis, 2024)
To realize good service quality, health centers must maintain the quality of their services, one way is to measure patient satisfaction. But in fact, the phenomenon that exists at the time of service at the Jajaway Health Center in Bandung City, patients still express a lack of health services provided at the health center such as waiting benches that are lacking so that patients waiting for the queue still have to stand, service hours that are still not on time, minimal information related to the health center and there are still officers who are less friendly during service. This study aims to determine Patient Satisfaction with Health Services (In Building) at the Jajaway Health Center, Bandung City. The type of research used is a quantitative method with a descriptive approach. The patient population in April 2023 in this study was 1294 respondents and the research sample used was 95 respondents. The data collection technique uses stratified random sampling. This research was conducted on July 14-19, 2023 at the Jajaway Health Center, Bandung City. The results of this study showed 2 respondents (2.1%) were very dissatisfied, 1 respondent (1.1%) was dissatisfied, 63 respondents (66.3%) were satisfied, and 29 respondents (30.5%) were very satisfied.